The improbable city: adaptations of an Arctic metropolis. (2nd October 2017) - Jull, Matthew
ABSTRACT: Starting as a remote and isolated Soviet Arctic outpost in the 1920s, development of Norilsk occurred rapidly after the discovery of vast amounts of nickel and other metal ores. Despite being located in one of the most extreme cold climates on Earth, the city's population increased from a few hundred to over 180, 000 over the course of about 50 years, making it the largest and most densely inhabited Arctic city built on permafrost. Serving as a de facto full-scale Arctic laboratory for architecture, urban design, and construction techniques, progress occurred at great cost to the workers and prisoners who built the city. The result – a hybrid of socialist classicism and modernist architecture and city planning adapted to extreme conditions – is in many ways as improbable and extreme as the Arctic environment itself. But beneath the apparently singular and uncompromising form of Norilsk lies an important legacy of effort to create a functional, efficient, and livable city in the Arctic. In this article, the historical arc of the development of Norilsk is synthesized and presented as a timeline and as a series of diagrams that explains the urban and architectural evolution that was necessary to accomplish this goal. This evolution is contextualized in relation to forces that were shaping the new Soviet city at the beginning of the twentieth century, providing a framework for understanding the development of future Arctic cities.